Some reflections on autobiography as an interpretative tool in the history of education - Southwell, Myriam (2022)
In contrast to more classical historiographical-educational currents, constituted by narratives in which a pristine will that embodied equally pristine pedagogical ideals prevailed, the new and reinforced versions of history highlight the ambiguous and contradictory character of political-pedagogical discourses. The narratives made available here do not refer to biographies of destiny, monolithic and finished; rather, they propose visions where life is traced as a trajectory, as a project, traversed by chance. In order to make these events intelligible, the toolbox used gradually includes more and more devices that allow us to approach the evanescent character of life, the account of vicissitudes or the account of events. To this end, autobiography comes to our aid to broaden the horizon of intelligibility.